EFFECTS OF Melastoma malabathricum COMPOST APPLICATION ON VEGETATIVE GROWTH OF Pennisetum purpureum cv. Thailand AND ITS SUITABILITY AS RUMINANT FEED - Naisya Zahratul Jannah; Neli Definiati; Wismalinda Rita; Lezita Malianti (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2026)
Feed availability is an important factor in increasing livestock productivity, especially in areas with limited land and low soil fertility. Pakchong grass (Pennisetum purpureum cv. Thailand) is a high-quality forage with good growth potential, but its optimal production requires proper soil nutrient management. This study aims to evaluate the effect of compost application derived from Melastoma malabathricum L. agricultural waste on the growth of Pakchong grass. The study was conducted from July 2024 to April 2025 at the UPTD-PPT Livestock and Animal Health Service in Bengkulu Province, using a randomized block design with four compost dose levels, namely 0 (control), 10, 20, and 30 tons/ha, each with three replicates. The variables observed included plant height, leaf width, stem diameter, and number of tillers measured at the first and second harvests. The data were analyzed using analysis of variance (ANOVA) followed by Duncan's Multiple Range Test. The results showed that the application of Melastoma malabathricum L. compost at all doses had no significant effect (P>0.05) on all growth variables of Pakchong grass at both harvest times. However, all variables increased numerically from the first to the second harvest, especially at higher compost doses. This indicates that Melastoma malabathricum L. compost plays a role in improving soil conditions and supporting the vegetative growth of Pakchong grass, although its effect is gradual and not yet significant in a relatively short observation period. Therefore, this compost has the potential to be used as an alternative for long-term sustainable fertilization in environmentally friendly forage production systems.